Treatment Options for Lipodystrophy in Children - Mainieri, Francesca; Tagi, Veronica Maria; Chiarelli, Francesco (Frontiers in Endocrinology, 2022)
Lipodystrophy includes a heterogeneous group of rare diseases characterized by different amounts of adipose tissue loss and several metabolic complications, including hypertriglyceridemia, steatohepatitis and particularly insulin resistance, that may lead to severe morbidity and, sometimes, mortality. Therefore, therapy for lipodystrophy primarily consists of a conventional approach that involves standard treatments of metabolic abnormalities. Given the evidence of leptin deficiency in lipodystrophy syndromes, leptin replacement therapy has been considered as a treatment option. Long-term studies on the use of therapy with a methionylated analog of human leptin, metreleptin, first on animals and subsequently on human patients, demonstrated enormous improvements of patients’ clinical features and metabolic conditions. Recently, metreleptin was approved by Food and Drug Administration (FDA) for the treatment of generalized lipodystrophy and by European Medicines Agency (EMA) for the treatment of both generalized and partial lipodystrophy. However, further research is being conducted for new and different therapeutic agents, especially helpful for the treatment of patients with partial lipodystrophy, as some of them do not have access to metreleptin therapy or show poor response.